(untitled) (Journal of Dhaka National Medical College & Hospital, 2017)
Vitriolage means throwing of any corrosive, not necessarily sulphuric acid, on a person with malicious intent. Here we present a case of 18 years old girl Rubina who was a victim of acid burn due to refusal of love proposal. She was admitted in the One Stop Crisis Center (OCC) of Dhaka Medical College Hospital. Acid burn injuries involved left half of the face, left side of the chest, left side of neck, left arm and left eye. Investigation was done and she was treated with first aid after vitriolage by plenty of water and soap, thick paste of magnesium oxide and eyes are washed with water and irrigated with a dilute sodium bicarbonate solution and instilled of eyes by few drops of olive oil. J. Dhaka National Med. Coll. Hos. 2017; 23 (02): 54-56